The Mechanism and Application of Deep-Hole Precracking Blasting on Rockburst Prevention - Zhenhua Ouyang; Qingxin Qi; Shankun Zhao; Baoyang Wu; Ningbo Zhang (Shock and Vibration)
The mechanism of preventing rockburst through deep-hole precracking blasting was studied based on experimental test, numerical simulation, and field testing. The study results indicate that the deep-hole precracking could change the bursting proneness and stress state of coal-rock mass, thereby preventing the occurrence of rockburst. The bursting proneness of the whole composite structure could be weakened by the deep-hole precracking blasting. The change of stress state in the process of precracking blasting is achieved in two ways: (1) artificially break the roof apart, thus weakening the continuity of the roof strata, effectively inducing the roof caving while reducing its impact strength; and (2) the dynamic shattering and air pressure generated by the blasting can structurally change the properties of the coal-rock mass by mitigating the high stress generation and high elastic energy accumulation, thus breaking the conditions of energy transfer and rock burst occurrence.